An introduction to enterprise architecture - Bernard, Scott A. (AuthorHouse, 2005)
This book provides a cursory treatment of a deep subject. At barely 250 pages of main body text--and they are small pages at that, set in a generous type--there is no room to go into detail on much of anything.